Utilization of Flexible Airspace Structure in Flight Efficiency Optimization - Mihetec, Tomislav; Steiner, Sanja; Odić, Denis (Promet - Traffic&Transportation, 2013)
With increasing air traffic demand in the Pan-European airspace there is a need for optimizing the use of the airspace structure (civilian and military) in a manner that would satisfy the requirements of civil and military users. In the area of Europe with the highest levels of air traffic (Core area) 32% of the volume of airspace above FL 195 is shared by both civil and military users. Until the introduction of the concept of flexible use of airspace, flexible airspace structures were 24 hours per day unavailable for commercial air transport. Flexible use of airspace concept provides a substantial level of dynamic airspace management by the usage of conditional routes. This paper analyses underutilization of resources, flexible airspace structures in the Pan-European airspace, especially in the south-eastern part of the traffic flows (East South Axis), reducing the efficiency of flight operations, as result of delegating the flexible structures to military users. Based on previous analysis, utilization model for flexible use of airspace is developed (scenarios) with defined airspace structure. The model is based on the temporal, vertical, and modular airspace sectorisation parameters in order to optimize flight efficiency. The presented model brings significant improvement in flight efficiency (in terms of reduced flight distance) for air carriers that planned to fly through the selected flexible airspace structure (LI_RST-49).